Online Platform-Based Digital Marketing Training to Enhance the Branding of Gula Saka Talang Anau - roza yunita; Firsta Ninda Rosadi; Wellyalina; Lusi Puspika Sari (Jurnal Hilirisasi IPTEKS, 2025)
Digital transformation is a key factor in enhancing the competitiveness of micro, small, and medium enterprises (MSMEs), particularly in rural areas that still face significant technological access gaps. This community engagement program aims to improve the digital literacy and skills of rural MSME actors producing gula saka (traditional brown sugar) through training on social media, online marketplaces, and Google Maps as tools for promotion and market expansion. The program employed a combination of pre-test, intensive hands-on training, and post-test to measure participants’ skill improvement. The training focused on digital branding, online marketing strategies, and business location mapping. Evaluation was conducted using a questionnaire covering three indicators: relevance, efficacy, and usefulness. The results show a substantial increase in participants’ digital skills, from 18% (pre-test) to 96% (post-test). The relevance indicator scored 3.6 out of 4, efficacy scored 3.0, and usefulness scored 4.0. Although no online transactions have occurred, the appearance of gula saka products on Google Maps indicates improved digital visibility. Participants perceived digital marketing as highly relevant and beneficial, although some challenges remain in applying these skills effectively. This program strengthens local branding and creates strategic opportunities for market expansion and gradual socio-economic impact. Continued mentoring is needed to ensure the consistent application of digital skills in business practices.